2020
DOI: 10.2166/wcc.2020.256
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based modeling of urban waterlogging in Khulna City

Abstract: Khulna City is extremely vulnerable to the effects of climate change. The city experiences frequent waterlogging during extreme rainfall events. This research prepared a drainage simulation model considering climate change issues for investigating the extent of waterlogging in the city. Watershed and precipitation were analyzed to examine the existing scenario of the study area. Finally, a Mike Urban-based hydrological simulation model was formulated to investigate the severity of waterlogging. As found by pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Bangladesh is already one of the world’s most vulnerable country to climate change induced natural disasters [ 9 , 10 ]. In terms of the risk of transmission of COVID-19, Haider et al [ 11 ] have classified Bangladesh into the 4th quantile (highest risk) based on the destinations of the passengers travelling from four major cities of China from January onwards.…”
Section: Introductionmentioning
confidence: 99%
“…Bangladesh is already one of the world’s most vulnerable country to climate change induced natural disasters [ 9 , 10 ]. In terms of the risk of transmission of COVID-19, Haider et al [ 11 ] have classified Bangladesh into the 4th quantile (highest risk) based on the destinations of the passengers travelling from four major cities of China from January onwards.…”
Section: Introductionmentioning
confidence: 99%
“…For intensity, most estimates an average from historical data, and the timespan for consideration can be annual [23], daily [23], or hourly [15]. For duration, minute-based [16,17], hourly [21,31,32,[60][61][62], daily [18,33,63], and multi-day-based [23] models are all reported. It is also noticed all studies made use of historical data, and realtime precipitation are only addressed in theoretical studies on data and system integration models [5,8,38].…”
Section: Hydrological Datamentioning
confidence: 99%
“…In 2014, more than 65,000 households were affected by rainfall-induced waterlogging disasters in the southern coastal districts only [7]. Sarkar et al [9] reported that 38% of coastal inhabitants in southern Khulna City experience short-term waterlogging every year. More recently, Chattogram, the most prosperous economic region of Southern Bangladesh, suffered its highest recorded economic damage of US $71 million caused by several waterlogging events in the single financial year of 2017 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al [20] applied a hydrodynamic model in Carlisle, Northwest England to assess the impact of a sustainable drainage system design for urban flood modeling. Sarkar et al [9] utilized a MIKE hydrological model for Khulna, Bangladesh and showed that both the existing drainage area and capacity are inadequate to mitigate waterlogging risk. Inspired by these previous studies of the dependence of waterlogging on various factors, including meteorological and hydrological, that have advanced the understanding of the waterlogging risk of many cities worldwide, the present study investigated the potential waterlogging risk in Chattogram City, Bangladesh.…”
Section: Introductionmentioning
confidence: 99%